Factores Socio-Políticos que limitan el aprovechamiento turístico del Cacao en el distrito de Chazuta - Chujandama Gaviria, Teodosio (2015)
In the present investigation, all information necessary and appropriate to show the current situation in which the district is located in Chazuta tourism issues is collected, raising an information closer to reality based on surveys of residents of the district and interviews with the direct actors of tourism in the district to develop. Experiences living communities opted for tourism development, considering it as a core activity, for its favorable income received these receptor sites and how this activity becomes a conduit for social inclusion is described. This research takes as a case study tourism development of cocoa and what their limitations for development in the district of Chazuta, in which it is stated that such limitations are the lack of authorities, limited tourist culture of its people and poor disorganization of cocoa associations; comprobándose by analyzing the tabulation of the results of the surveys in a picture or graphic illustration. Before that problem over a proposal in which the importance of training and awareness among stakeholders in tourism and how to deploy to the estates of cocoa plantations to be eligible to receive domestic and foreign visitors is highlighted arises; for the preparation of this proposal as indirect information sources and websites that mention references to related topics at research was compiled, this research suggests an alternative for tourism in the region San Martin diversifying the tourism product of the region. That is why the need for further investigation of this topic , involving communities and makes witness the importance of handling guidelines for the proper development and how to build a sustainable tourism management in the area of study.